Gingival tissue, an extrasynovial source of malondialdehyde‐acetaldehyde adducts, citrullinated and carbamylated proteins. (17th October 2017) - Bright, R.; Thiele, G. M.; Manavis, J.; Mikuls, T. R.; Payne, J. B.; Bartold, P. M.
Abstract : Background and Objective: Postranslational modification of proteins can lead to the production of autoantibodies and loss of immune tolerance. This process has been hypothesised to be a critical factor in the pathogenesis of rheumatoid arthritis. The objective of this study was to demonstrate that inflamed human gingival tissue provides an extrasynovial source of malondialdehyde‐acetaldehyde adducts, citrullinated and carbamylated proteins all of which are considered to be linked to the development of rheumatoid arthritis. Identification of such modified proteins in inflamed gingiva may explain, in part, how inflammation of the periodontal tissues may influence the development of rheumatoid arthritis. Material and Methods: Gingival biopsies of healthy, mild and moderate periodontitis were triple stained with antibodies against malondialdehyde‐acetaldehyde adducts, citrullinated and carbamylated proteins. Results: Assessment of healthy gingival tissue revealed negligible staining for carbamylated, malondialdehyde‐acetaldehyde (MAA), or citrullinated proteins. Mild periodontitis was positive for all three modifications. Furthermore, there was an increase in staining intensity for carbamylated, citrullinated and MAA‐modified proteins in moderate periodontitis. Negative staining results were observed for the isotype controls. Conclusion: This study provides evidence for the presence of citrullinated, carbamylated and MAA adduct modified proteins in inflamed periodontal tissues. The potential for these proteins to play a role in autoimmunity in a multi‐system inflammatory syndromic disease model now needs to be determined.